2006
DOI: 10.14358/pers.72.3.313
|View full text |Cite
|
Sign up to set email alerts
|

Capability of SRTM C- and X-band DEM Data to Measure Water Elevations in Ohio and the Amazon

Abstract: I analyze Shuttle Radar Topography Mission (SRTM) water surface elevation data to assess the capacity of interferometric radar for future surface water missions. Elevations from three Ohio reservoirs and several Amazon floodplain lakes have standard deviations, interpreted as errors, that are smaller in C-band compared to X-band and are smaller in Ohio than in the Amazon. These trends are also evident when comparing water surface elevations from the Muskingum River in Ohio with those of the Amazon River. Diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…The approach used by SWOT is similar to that of LeFavour and Alsdorf (2005) and Kiel et al (2006), who used Shuttle Radar Topography Mission (SRTM) elevation data of the water surface to obtain slopes of the Amazon and Ohio rivers and, subsequently, to estimate channel discharge. However, for the Amazon, LeFavour and Alsdorf (2005) found vertical errors of 5.51 m in water-surface elevations from Cband SRTM data, meaning that a long-reach length of 733 km was required to reduce errors in derived water-surface slopes to 1.5 cm km −1 for the accurate estimation of channel discharge (6.2 % error at Manacapuru; 7.6 % at Itapeua).…”
Section: D Wilson Et Al: Swath-altimetry Measurements Of the Maimentioning
confidence: 99%
“…The approach used by SWOT is similar to that of LeFavour and Alsdorf (2005) and Kiel et al (2006), who used Shuttle Radar Topography Mission (SRTM) elevation data of the water surface to obtain slopes of the Amazon and Ohio rivers and, subsequently, to estimate channel discharge. However, for the Amazon, LeFavour and Alsdorf (2005) found vertical errors of 5.51 m in water-surface elevations from Cband SRTM data, meaning that a long-reach length of 733 km was required to reduce errors in derived water-surface slopes to 1.5 cm km −1 for the accurate estimation of channel discharge (6.2 % error at Manacapuru; 7.6 % at Itapeua).…”
Section: D Wilson Et Al: Swath-altimetry Measurements Of the Maimentioning
confidence: 99%
“…DEM only represents the terrain, as it was at the time of data acquisition; hence any change on the ground surface made afterward would be absent in a DEM. Additionally, river longitudinal channel slope is often calculated from DEM elevations along the river [25,26]. It was observed that longitudinal channel slope (over entire study reach) calculated from base NED was more reliable than that of base SRTM.…”
Section: Discussionmentioning
confidence: 99%
“…SAR interferometry is an imaging method to measure the altitude of lake levels (Alsdorf et al, 2006). In-SAR data are a first step towards the simultaneous measurement of a water surface's elevation and areal extend (Alsdorf & Lettenmaier, 2003).…”
Section: State Of the Artmentioning
confidence: 99%
“…In-SAR data are a first step towards the simultaneous measurement of a water surface's elevation and areal extend (Alsdorf & Lettenmaier, 2003). Investigating SRTM data, Kiel et al (2006) found that errors for C-band are smaller than for X-band. Overlaying multispectral scenes on high resolution DEMs is another approach to combine area and elevation measurements (Alsdorf et al, 2006).…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation